Low potential of circulating interleukin 1 receptor antagonist as a prediction marker for squamous cell carcinoma of the head and neck. (9th May 2021) - Boldrup, Linda; Coates, Philip; Gu, Xiaolian; Wang, Lixiao; Fåhraeus, Robin; Wilms, Torben; Sgaramella, Nicola; Nylander, Karin
Abstract: Background: Circulating markers are attractive molecules for prognosis and management of cancer that allow sequential monitoring of patients during and after treatment. Based on previous protein profiling data, circulating interleukin 1 receptor antagonist (IL‐1Ra) was evaluated as a potential diagnostic and prognostic marker for squamous cell carcinomas of the head and neck (SCCHN). In this study, we aimed at confirming the clinical relevance of plasma IL‐1Ra in SCCHN and exploring its potential as a prediction marker for SCCHN. Methods: Plasma from 87 patients with SCCHN, control plasma from 28 healthy individuals and pre‐diagnostic plasma from 44 patients with squamous cell carcinoma of the oral tongue (SCCOT) and 88 matched controls were analysed with IL‐1Ra electrochemiluminescence immunoassays from mesoscale diagnostics. Results: Plasma IL‐1Ra was found to be up‐regulated in patients with oral tongue, gingiva and base of tongue tumours compared to healthy individuals ( p < 0.01). IL‐1Ra levels positively correlated with tumour size ( p < 0.01) and body mass index ( p = 0.013). Comparing pre‐diagnostic plasma to the matched controls, similar IL1‐Ra levels were seen ( p = 0.05). Conclusion: The anti‐inflammatory cytokine IL‐1Ra could be a diagnostic marker for SCCHN, whereas its potential as a cancer prediction marker was not supported by our data.